The Disorazole Z Family of Highly Potent Anticancer Natural Products from Sorangium cellulosum: Structure, Bioactivity, Biosynthesis, and Heterologous Expression - Yunsheng Gao; Joy Birkelbach; Chengzhang Fu; Jennifer Herrmann; Herbert Irschik; Bernd Morgenstern; Kerstin Hirschfelder; Ruijuan Li; Youming Zhang; Rolf Jansen; Rolf Müller (Microbiology Spectrum, 2023)
ABSTRACT Myxobacteria serve as a treasure trove of secondary metabolites. During our ongoing search for bioactive natural products, a novel subclass of disorazoles termed disorazole Z was discovered. Ten disorazole Z family members were purified from a large-scale fermentation of the myxobacterium Sorangium cellulosum So ce1875 and characterized by electrospray ionization–high-resolution mass spectrometry (ESI-HRMS), X-ray, nuclear magnetic resonance (NMR), and Mosher ester analysis. Disorazole Z compounds are characterized by the lack of one polyketide extension cycle, resulting in a shortened monomer in comparison to disorazole A, which finally forms a dimer in the bis-lactone core structure. In addition, an unprecedented modification of a geminal dimethyl group takes place to form a carboxylic acid methyl ester. The main component disorazole Z1 shows comparable activity in effectively killing cancer cells to disorazole A1 via binding to tubulin, which we show induces microtubule depolymerization, endoplasmic reticulum delocalization, and eventually apoptosis. The disorazole Z biosynthetic gene cluster (BGC) was identified and characterized from the alternative producer S. cellulosum So ce427 and compared to the known disorazole A BGC, followed by heterologous expression in the host Myxococcus xanthus DK1622. Pathway engineering by promoter substitution and gene deletion paves the way for detailed biosynthesis studies and efficient heterologous production of disorazole Z congeners. IMPORTANCE Microbial secondary metabolites are a prolific reservoir for the discovery of bioactive compounds, which prove to be privileged scaffolds for the development of new drugs such as antibacterial and small-molecule anticancer drugs. Consequently, the continuous discovery of novel bioactive natural products is of great importance for pharmaceutical research. Myxobacteria, especially Sorangium spp., which are known for their large genomes with yet-underexploited biosynthetic potential, are proficient producers of such secondary metabolites. From the fermentation broth of Sorangium cellulosum strain So ce1875, we isolated and characterized a family of natural products named disorazole Z, which showed potent anticancer activity. Further, we report on the biosynthesis and heterologous production of disorazole Z. These results can be stepping stones toward pharmaceutical development of the disorazole family of anticancer natural products for (pre)clinical studies.